Raconter le care ? À propos de L'homme ralenti de John M. Coetzee - Marzi, Laura (Perspectives du care, 2022)
John M. Coetzee's novel "Slow Man" depicts a care relationship between Paul Rayment, an accident victim with a disability, and his home helper Marijana. Transformed into a field investigation, this novel allows us to study the link between care and literature. It also features domestic workers (nannies, care assistants, home helpers), revolutionising the symbolic order and overturning their invisible status. Drawing on feminist literary criticism, and based on the character of the care worker, the author considers the deconstruction of the notion of heroism, by proposing instead the notion of "heroinism". This study aims to convince readers of the importance of integrating contemporary care issues into literary studies and of the usefulness of critically questioning the distinction often made between "fiction" and "reality". Laura Marzi has a PhD in gender studies and comparative literature and is a literary critic, writer and translator. Active in the Italian feminist scene and in the press, she has published several scientific articles and translations.